2020
DOI: 10.1007/s11618-019-00922-z
|View full text |Cite
|
Sign up to set email alerts
|

Who sticks to the instructions—and does it matter? Antecedents and effects of students’ responsiveness to a classroom-based motivation intervention

Abstract: Why do some students benefit from interventions and others do not? By investigating the antecedents and effects of students' responsiveness to a classroombased motivation intervention, the current study aims to shed light on the intervention processes that make educational interventions in real-life settings work. Using data from a cluster-randomized controlled experiment with 1916 ninth-grade students, students' responsiveness to two written intervention activities about the personal relevance of mathematics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…With respect to relevance-inducing reflection tasks, this approach asks students to reflect upon the relevance of the learning material to their lives and to make specific, personal connections (Brisson et al, 2020;Harackiewicz et al, 2016;Hulleman et al, 2017). Several studies with high school (Hulleman & Harackiewicz, 2009) and college students (Canning et al, 2018;Harackiewicz et al, 2016;Hulleman et al, 2010Hulleman et al, , 2017Kosovich et al, 2019;Rosenzweig et al, 2020) have shown that this intervention approach yields positive effects on utility value, interest, and performance, although the effects are often limited to students at risk for low motivation (i.e., students with low expectancies; e.g., Hulleman et al, 2010Hulleman et al, , 2017Hulleman & Harackiewicz, 2009; or students from minority groups; e.g., Harackiewicz et al, 2016).…”
Section: Relevance Interventions: Prior Research and Remaining Questions Before Bringing Them To Scalementioning
confidence: 99%
“…With respect to relevance-inducing reflection tasks, this approach asks students to reflect upon the relevance of the learning material to their lives and to make specific, personal connections (Brisson et al, 2020;Harackiewicz et al, 2016;Hulleman et al, 2017). Several studies with high school (Hulleman & Harackiewicz, 2009) and college students (Canning et al, 2018;Harackiewicz et al, 2016;Hulleman et al, 2010Hulleman et al, , 2017Kosovich et al, 2019;Rosenzweig et al, 2020) have shown that this intervention approach yields positive effects on utility value, interest, and performance, although the effects are often limited to students at risk for low motivation (i.e., students with low expectancies; e.g., Hulleman et al, 2010Hulleman et al, , 2017Hulleman & Harackiewicz, 2009; or students from minority groups; e.g., Harackiewicz et al, 2016).…”
Section: Relevance Interventions: Prior Research and Remaining Questions Before Bringing Them To Scalementioning
confidence: 99%
“…Related insights have also been found in the utility‐value literature. Studies consistently demonstrate that the effectiveness of utility‐value interventions depends on the frequency and quality with which students make different connections between course material and their lives (Brisson et al, 2020; Hulleman et al, 2017, 2021). Such findings may be explained by related research demonstrating that the collative properties of situations, such as novelty and complexity, increase arousal (Berlyne, 1969), which can then lead to positive affect and situational interest (Hidi & Renninger, 2006) and in turn persistence and performance (Canning et al, 2018).…”
Section: Backgroudmentioning
confidence: 99%
“…Ezen felül módszertani kihívás annak kezelése is, hogy a pedagógusok vagy más, a pedagógiai gyakorlatban dolgozó szakemberek valóban az elvárások szerint hajtják-e végre a kidolgozott intervenciót (Fullan, 2001;Greshem et al, 2000). Ennek részletes dokumentálása egyre erősebb elvárás (Brisson et al, 2020;Hulleman & Cordray, 2009;Murrah et al, 2017).…”
Section: Finanszírozási éS Szervezési Kérdésekunclassified